1980
DOI: 10.1038/bjc.1980.138
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma: social status and outdoor work

Abstract: Summary. The incidence of, and mortality from, malignant melanoma of skin in whites are strongly influenced by socio-economic conditions. Professional and administrative workers have the highest rates of all. Clerks and salesmen have higher rates than skilled manual workers, who have higher rates than unskilled workers.Women, when classified by the occupation of their husbands, show a similar relationship to social status.The biases of incidence data from systems of cancer registration, and mortality data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
51
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 20 publications
5
51
0
Order By: Relevance
“…In particular, such differences would not explain the contrast between office and non-offlce indoor workers within the same social class which have now been suggested by three studies (this one; Lee & Strickland, 1980;Beral & Robinson, 1981). However, the possibility that within each social class, patterns of sunlight exposure and experience of sunburn are different in office, other indoor and outdoor workers, could not be entirely ruled out.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In particular, such differences would not explain the contrast between office and non-offlce indoor workers within the same social class which have now been suggested by three studies (this one; Lee & Strickland, 1980;Beral & Robinson, 1981). However, the possibility that within each social class, patterns of sunlight exposure and experience of sunburn are different in office, other indoor and outdoor workers, could not be entirely ruled out.…”
Section: Discussionmentioning
confidence: 85%
“…It is more common in upper than in lower social classes (Logan, 1982;Lee & Strickland, 1980;Vager6 & Persson, 1984). It is not known why this is the case but it is usually assumed that this is due to different patterns of sun exposure and holiday travel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is particularly clear when data for a relatively homogeneous socio-economic group (social class III) are examined (Table IV). Although others have noted a high rate of all melanomas in office workers (Lee & Strickland, 1980), it has not been recognized before that this is because of an especially high rate of lesions on the unexposed parts of the body. Office workers contrast clearly with other indoor workers, who generally have below-average rates of melanomas, squamous-and basal-cell cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In another case-control study Lancaster & Nelson (1957) found no such association. Analyses of vital statistical data consistently reveal high melanoma rates in professional and other occupational groups engaged in indoor office work (Lee & Strickland, 1980;Holman et al, 1980). In contrast farmers and fishermen have melanoma mortality rates below the national average, suggesting that working out of doors is not necessarily associated with an increase in melanoma.…”
mentioning
confidence: 99%